Original paperAcne in hirsute women - Lumezi, Besa Gacaferri; Pupovci, Hatixhe Latifi; Berisha, Violeta Lokaj; Goçi, Aferdita Uka; Gerqari, Antigona (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction: Acne and hirsutism are common manifestations of hyperandrogenism. Aim: To investigate whether or not acne is present in women with hirsutism, associated with different clinical, endocrine and ultrasonographic features.  Material and methods: The prospective study included 135 women with hirsutism, aged 14–46 years. We measured the levels of hormones with radioimmunoassay/immunoradiometric assay methods. Results: Acne were present in 63 (47.6%) women with hirsutism. Sixty women had mild forms of acne, including: whiteheads, blackheads, papules and pustules. Only 3 women had moderate to severe acne, including nodules. In a group of women with hirsutism and acne, 6 (9.5%) were obese. In our study we found a high prevalence of androgen excess among hirsute women with acne: total testosterone was increased in 79%, free testosterone in 20.6%, androstenedione in 69.8%, dehydroepiandrosterone sulfate (DHEAS) in 30.1%, 17-OH-progesterone 68.2% and sex hormone-binding globulin (SHBG) was decreased in 33.3% of women. Women with hirsutism and acne have received oral contraceptives for a year, without or in a combination with other medication. Thirty-four (53.9%) women have shown improvement in hirsutism and acne. Conclusions : In this study we found a high prevalence of acne in hirsute women. The prevalence of acne was higher in polycystic ovarian syndrome. Since these women have associated endocrine changes it is important to correct them with hormonal therapy.